A Case Study in Corporate Social Responsibility - Kendrick, Sharon K.; Kendrick, Mark; Saakova, Anastasiya (Journal of Eastern European and Central Asian Research (JEECAR), 2014)
This case study promotes analysis through a brief investigation into the role of corporate social responsibility (CSR) in the operation of a multinational corporation as evidenced by Google, Inc. The study focuses on a transnational company in order to observe the impact of CSR practice on a global level. The study will present implications of CSR for corporate management, corporate employees, state regulators, shareholders, and customers in general. In addition, the study will discuss consequences of poor CSR compliance for a multinational corporation. Questions for analysis include implications of CSR, employee retention, development of corporate culture, and evaluation of advantages and disadvantages of different CSR approaches. Upon conclusion of the study, suggestions are made for future collaborative efforts in corporate social responsibility as applied to psychological, sociological, and economical motives. Recruiting and training possibilities also present partnership opportunities for best practice sharing in regards to community, civic, and service engagement.